Estudo computacional da enzima gGAPDH do Trypanosoma cruzi - Oliveira, Osmair Vital de (Universidade Federal de São Carlos, 2009)
Theoretical methods in computational chemistry were used to study the gGAPDH enzyme from Trypanosoma cruzi. This protozoan is responsible by the Chagas diseases. Molecular dynamics simulations were performed to obtain the time evolution of the gGAPDH enzyme in the holo (with the cofactor NAD+) and apo (without the cofactor) forms in aqueous solution. The calculations were performed in the NpT ensemble with T = 300K e p = 1bar. In these simulations little conformational changes were observed in both holo and apo forms of the enzyme along 20.0 ns simulation time. Docking calculations were carried out to fit some drugs in enzyme active site using the ensemble docking methodology. Therefore, multiple enzyme conformations of both holo and apo forms were obtained at time intervals of 2.0 ns along the molecular dynamics simulation. This procedure was used to take in into account the flexibility of the enzyme. The results from these calculations indicate that the best way to develop a drug molecule is to consider both enzyme forms (holo and apo forms). In this way, one drug will inhibit the apo form and other, the holo form. To characterize the enzymatic mechanism, the glyceraldehyde 3-phosphate (G3P) was placed in the active site (via docking calculations) of the holo form conformation obtained in the end of the 20.0 ns trajectory. A 1.0 ns molecular dynamic simulation was performed in the (gGAPDH-NAD+-G3P) system. Quantum chemical calculations were performed to study reactive process in the enzyme catalytic site. A convenient model was built using about 698 atoms carefully chosen to represent the active site and its surroundings. The calculations were performed using a combination of MOZYME and the usual SCF procedure implemented in the MOPAC2009 program. The calculations were performed at the PM6 level. One of the reaction mechanisms proposed in the literature was characterized xix calculating the energy profile along the reaction path to transfer a proton from Cys166 to His194. Using a second structure obtained from molecular dynamics, a new mechanism for the gGAPDH enzyme was proposed and characterized by a similar MOPAC2009 calculation. In this mechanism, the hydroxyl group of the G3P acts as a bridge to transfer the proton from the Cys166 to His194 residue.
Computational study of the gGAPDH enzyme from Trypanosoma cruzi
Keywords: Química quântica; Dinâmica molecular; Docking; GAPDH; Trypanosoma cruzi; CIENCIAS EXATAS E DA TERRA::QUIMICA